Revitalisasi Panglima Uteun dalam Pengelolaan Hutan di Kabupaten Aceh Besar - Mahmuddin, Mahmuddin; Januar, Eka; Mansari, Mansari (Sociology Department Of Syiah Kuala University, 2024)
Local customary-based forest management holds significant potential for supporting ecological sustainability and the well-being of surrounding communities. Panglima Uteun, as a customary institution, plays a strategic role in maintaining ecological balance and community welfare. Therefore, it is crucial to revitalize the role of Panglima Uteun as a vital component of social capital in sustainable forest management. This study adopts a qualitative approach, utilizing data collected through observation, in-depth interviews, Focus Group Discussions (FGDs), and documentation studies. The research focuses on forest areas in Jantho City, Aceh Besar. Data validity is ensured through triangulation to verify the accuracy of the information. The findings reveal that Panglima Uteun plays a strategic role in forest management, including leading the implementation of forest-related customs, enforcing customary laws, and maintaining ecological balance. However, the existence of Panglima Uteun faces challenges from modernization, market pressures, and limited support for customary institutions. Violations of customary norms, such as illegal logging and unauthorized land clearing, emerge as major issues requiring stronger synergy among local communities, Panglima Uteun, and local governments. This study underscores the importance of revitalizing the role of Panglima Uteun as social capital to support sustainable community-based forest management. The integration of customary norms, institutional networks, and the active participation of local communities can be key to successful forest conservation. Policies that strengthen the position of customary institutions in forest governance are necessary to preserve the ecology, economy, and local culture of Aceh Besar.AbstrakPengelolaan hutan berbasis adat lokal memiliki potensi besar dalam mendukung keberlanjutan ekologi dan kesejahteraan masyarakat di sekitarnya. Dalam konteks pengelolaan hutan berbasis norma adat, Panglima Uteun memiliki peran strategis untuk menjaga keseimbangan ekologi hutan dan kesejahteraan masyarakat. Sehingga diperlukan upaya revitalisasi peran Panglima Uteun sebagai modal sosial dalam pengelolaan hutan yang berkelanjutan. Penelitian ini menggunakan pendekatan kualitatif dengan pengumpulan data melalui observasi, wawancara mendalam, Focus Group Discussions (FGD), dan studi dokumentasi. Lokasi penelitian berfokus pada kawasan hutan di Kota Jantho, Aceh Besar. Validitas data dijaga dengan metode triangulasi untuk memastikan keabsahan informasi. Hasil penelitian menunjukkan bahwa Panglima Uteun memainkan peran strategis dalam pengelolaan hutan, termasuk memimpin pelaksanaan adat terkait hutan, menegakkan hukum adat, dan menjaga keseimbangan ekologi. Meski demikian, eksistensi Panglima Uteun menghadapi tantangan berupa modernisasi, tekanan pasar, dan lemahnya dukungan terhadap kelembagaan adat. Pelanggaran adat seperti penebangan liar dan pembukaan lahan tanpa izin menjadi isu utama yang membutuhkan sinergi lebih kuat antara masyarakat, Panglima Uteun, dan pemerintah daerah. Penelitian ini menegaskan pentingnya revitalisasi Panglima Uteun sebagai modal sosial untuk mendukung pengelolaan hutan berbasis komunitas yang berkelanjutan. Integrasi norma adat, jejaring kelembagaan, dan peran aktif komunitas lokal dapat menjadi kunci keberhasilan dalam melestarikan hutan. Diperlukan kebijakan yang memperkuat posisi kelembagaan adat dalam tata kelola hutan untuk menjaga ekologi, ekonomi, dan budaya lokal masyarakat Aceh Besar.